Pengembangan Gim Android Visual Novel Cerita Rakyat Reog Ponorogo berbasis Renpy untuk Meningkatkan Minat Baca Siswa SD Bangunsari 1 Ponorogo - Alif Wildan Chrisandy; Lutfi Fanani; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Games are increasingly in demand day by day. However, people's understanding of the history of the area is decreasing. This is evidenced by the less and less young people who understand how the history of the region can happen, such as the story of Reog, although it is famous, there are still many Ponorogo residents, especially the younger generation who lack know how the reog dance happened and how it originated.This study aims to determine whether there are differences in knowledge and interest in reading at Elementary School Bangunsari 1 Ponorogo. In this study, a purposive sampling method was used for data collection and the GDLC ( Game Development Life Cycle ) method for game application development.This research was conducted by comparing children's knowledge about reog before and after testing with the game. The game to be made is a visual novel game where the game is centered on story-telling.The results of this study indicate that children's knowledge increases when they play the reog game, but the game is still less attractive to the students of SD Bangunsari 1 Ponorogo due to the lack of action in the game..